Business Cycles in Korea: Is there any stylised feature? - Kim, Kunhong (School of Management Working Papers, 1994)
This paper seeks to present the detailed empirical study of contemporary business fluctuations in Korea. It follows the methodology of modem business cycle research in conducting an atheoretical statistical analysis of the cyclical properties of key aggregate time series. Analysis shows that many of the cyclical regularities documented for developed countries also exist in Korean business cycles. Those regularities include the relative volatilities of many expenditure components and the co-movement of real and nominal variables with output. Particularly notable one is the counter-cyclicality of prices. Counter-cyclicality of prices signals the importance of supply side shocks in Korean business fluctuations. It has been revealed in the analysis that the fluctuation in the import price of oil may have been the major source of Korean business cycles. Analysis has also revealed that there are some idiosyncrasies in Korean business cycles. Net exports are significantly pro-cyclical and lead the cycle for most of the period under study.